Resveratrol from Dietary Supplement to a Drug Candidate: An Assessment of Potential - Shivani Khattar; Sauban Ahmed Khan; Syed Amir Azam Zaidi; Mahdi Darvishikolour; Uzma Farooq; Punnoth Poonkuzhi Naseef; Mohamed Saheer Kurunian; Mohammed Zaafar Khan; Athar Shamim; Mohd Masih Uzzaman Khan; Zeenat Iqbal; Mohd. Aamir Mirza (MDPI AG, 2022)
Resveratrol (RVT) is a well known phyto-chemical and is widely used in dietary supplements and botanical products. It shows a wide range of pharmacological/beneficial effects. Therefore, it can be a potential candidate to be developed as phyto-pharmaceutical. Multiple diseases are reported to be treated by the therapeutic effect of RVT since it has antioxidant, anti-cancer activity and anti-inflammatory activities. It also has a major role in diabetes, arthritis, cardiac disorder and platelet aggregation etc. The major requirements are establishments regarding safety, efficacy profile and physicochemical characterization. As it is already being consumed in variable maximum daily dose, there should not be a major safety concern but the dose needs to be established for different indications. Clinical trials are also being reported in different parts of the world. Physicochemical properties of the moiety are also well reported. Moreover, due to its beneficial effect on health it leads to the development of some intellectual property in the form of patents.